MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PERISTIWA SEKITAR PROKLAMASI 17 AGUSTUS 1945 MELALUI METODE DISKUSI PADA PELAJARAN SEJARAH KELAS XII IPS 1 SMAN 3 TANJUNG TAHUN PELAJARAN 2011/2012 - Noorlan Noorlan (Universitas Lambung Mangkurat, 2013)
This Research told about the assumption what if these lessons are taught by professional teachers. In generally, the lessons of history will make students more eager, joyful and meaningful, so that the students know the significance of the history of the nation. The study used action research method during two cycles. The first cycle of research results from 27 states who attended the liveliness of the togetherness in the learning process in cycle 1 with an average value of 6.1 (enough), while in cycle 2 with an average value of 7.1 (good). Learning outcomes complete the first cycle yan 85.19%, while in the second cycle of the complete 96.15% .Ternyata after using the discussion an increase in activity and student learning outcomes. It shows that the lessons of history with discussion method will increase the activity and student learning outcomes in class XII IPS 3 SMAN 1 20011/20012 Tanjung school year.Key words: Activity, learning achievement, discuss method